ANTAGONISTIC EFFECT OF MUSK ON ORGANISMS DIFFERENT TYPES - ALJURISS, JANA ABDUL MOHSEN; ALNAJEM, NOURA SAUD; ALGHOFAILI, FAHDAH FAHAD; AL-ARIFI, TURKI N.; AL-KHATTAF, FATIMAH S. (International Journal of Current Pharmaceutical Research, 2020)
Objective: This study aims to The research aimed at a comparative study the effect of natural and synthetic musk compared to creams that have an anti-fungal and anti-bacterial effect on the growth of Candida albicans that causes vaginal diseases in women, as well as the growth of the bacteria strains include Staphylococcus aureus, Bacillus subtilis, which would be more effective in inhibiting the growth of these microbes and Achieve the recommendation of the Prophet Muhammad for women to treat the vagina with natural musk, find alternatives to synthetic antibiotics, and reduce their negative effects on human health. Methods: This study investigates the antagonistic effect of Anti fungal and bacterial Cream and different natural type Musk (N. M), Black Musk (B. M) and chemical Musk white Musk (W. M), cream Musk (M. C) on some microorganisms. The types of yeast Candida albicans HVS and the bacteria strains include Staphylococcus aureus, Bacillus subtilis, were tested by means of disk diffusion, Results: Results indicated that Musk has inhibitory effects on the growth of study microorganisms Musk contains active substances similar to antibiotic, alkaloids and volatile oils present in them as they have the ability to stop the growth of many microorganisms. The effect of natural musk was higher than the effect synthetic musk, And the microbes were the most sensitive to musk is Bacillus subtilis. As for anti-microbial creams, the effect of the anti-bacterial cream was more effective in their suppression compared to all kinds of musk unlike the anti-fungal cream which gave a negative result. Conclusion: This study showed that the different concentrations of natural musk have an effective role in inhibiting some of the microbes of this vaginal pathogen, and it has given a positive opposite result to these microbes, and therefore it can be used as a natural antibiotic that reduces side effects on females and the environment.